2002
DOI: 10.1002/bit.10430
|View full text |Cite
|
Sign up to set email alerts
|

Reduction kinetics of Fe(III), Co(III), U(VI), Cr(VI), and Tc(VII) in cultures of dissimilatory metal‐reducing bacteria

Abstract: The reduction kinetics of Fe(III)citrate, Fe(III)NTA, Co(III)EDTA-, U(VI)O(2) (2+), Cr(VI)O(4) (2-), and Tc(VII)O(4) (-) were studied in cultures of dissimilatory metal reducing bacteria (DMRB): Shewanella alga strain BrY, Shewanella putrefaciens strain CN32, Shewanella oneidensis strain MR-1, and Geobacter metallireducens strain GS-15. Reduction rates were metal specific with the following rate trend: Fe(III)citrate > or = Fe(III)NTA > Co(III)EDTA- >> UO(2)(2+) > CrO(4)(2-) > TcO(4)(-), except for CrO(4) (2-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
206
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(229 citation statements)
references
References 49 publications
20
206
2
1
Order By: Relevance
“…These observations complement prior observations of extracellular uraninite aggregates with individual nanometer-sized particles observed for these genera (2,3,5,23,24).…”
Section: Resultssupporting
confidence: 89%
“…These observations complement prior observations of extracellular uraninite aggregates with individual nanometer-sized particles observed for these genera (2,3,5,23,24).…”
Section: Resultssupporting
confidence: 89%
“…Hence, dependencies are expected to vary across microbial species and strains, and optimum conditions are likely to depend on the specific site conditions. Dissolved U(VI) is considerably more bioavailable for reduction than adsorbed and precipitated or solid-phase U(VI) (Liu et al 2006;Ortiz-Bernad et al 2004), which is analogous to the trend of soluble Fe(III) being more bioavailable and thus rapidly reduced by microorganisms than solid-phase Fe(III) oxides (Liu et al 2002).…”
Section: Introductionmentioning
confidence: 82%
“…Although the overall rates of microbial metal reduction may strictly follow Monod or Michaelis-Menten kinetics, at nongrowth conditions a first-order rate model approximation of Monod kinetics has been demonstrated to provide equally good fits to experimental data as Monod kinetics (Liu et al 2002). Other studies of microbial U(VI) reduction rates have also found good fits of first-order rate models to experimental data ).…”
Section: Reduction Rate Calculationmentioning
confidence: 97%
“…In the case where the reduction rate is slower due to the lower initial selenate concentration, the elemental selenium seed-nanoparticles have time to be transported out of the cell and therefore interfere less with the reduction reaction. It has been shown in another study [27] that elemental selenium seed-nanoparticles can physically get in the way of different steps in the reaction chain, for example blocking the redox enzyme or interfering with the intermediate electron transfer sites. These seed-nanoparticles can also negatively influence the porosity of the cell membrane.…”
Section: Kinetic Batch Experimentsmentioning
confidence: 99%